Implementation of Detailed Spatial Planning in Business Licensing in The Singaraja Urban Area - Desak Komang Sri Adnyani; I Wayan Rideng; Ni Komang Arini Styawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
This study analyzes the implementation of a detailed spatial plan integrated with the business licensing system in the urban area of Singaraja, which is now run through the Online Single Submission Risk Based Approach (OSS RBA) system. The purpose of this study is to analyze the mechanism for implementing business licensing and examine the legal consequences for business actors who do not comply with the provisions of the RDTR. The method used is empirical legal research with a legislative, sociological, and analytical approach. Data were obtained through interviews, observations, and document studies at the Investment and One-Stop Integrated Service Office, the Public Works and Spatial Planning Office of Buleleng Regency and several business actors in the urban area of Singaraja. The results of the study show that normatively and administratively, the implementation of Buleleng Regent Regulation Number 5 of 2021 has increased licensing efficiency and service transparency. However, its implementation has not been fully effective, as seen from the ongoing violations of the RDTR, weak law enforcement, and incomplete integration of the RDTR with the KBLI in the Online Single Submission Risk Based Approach (OSS RBA). Violations of the provisions of the RDTR can result in legal consequences in the form of administrative sanctions. However, the sanctions have not been implemented effectively because they are still under review.